การประเมินหลักสูตรปฐมนิเทศพนักงานใหม่ในบริษัทโทรคมนาคม - พากเพียรกิจ, วีรวัฒน์; ขมวัฒนา, อ.ดร.เพิ่มเกียรติ (An Online Journal of Education, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ ประเมินหลักสูตรปฐมนิเทศพนักงานใหม่ในบริษัท โทเทิ่ลแอ็คเซสคอมมูนิเคชั่น จำกัด ตามกรอบการประเมินแบบซิป ( CIPP Model ) เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบวิเคราะห์เอกสาร และ แบบประเมินหลักสูตร จำนวน 3 ชุด ผู้ให้ข้อมูลประกอบด้วย ผู้จัดการอบรม วิทยากร และผู้ช่วยวิทยากร ผู้เข้ารับการอบรมปฐมนิเทศ และ หัวหน้าผู้เข้ารับการอบรมปฐมนิเทศ รวมทั้งสิ้น จำนวน 72 คน วิเคราะห์ข้อมูลโดยคำนวณค่าร้อยละ ค่าเฉลี่ย และ ส่วนเบี่ยงเบนมาตราฐาน ผลการวิจัยปรากฏดังนี้ 1. การประเมินบริบท พบว่า วัตถุประสงค์ของหลักสูตรมีความสอดคล้องกับปัจจัยภายนอก ในด้านการนำเทคโนโลยีที่เรามีอยู่ เข้าช่วยเหลือสังคมในด้านต่างๆ วัตถุประสงค์และโครงสร้างของหลักสูตร เกณฑ์การวัดและประเมินผลการฝึกอบรม มีความเหมาะสมอยู่ในระดับมาก 2. การประเมินปัจจัยเบื้องต้น พบว่า ในด้านวิทยากร ผู้เข้ารับการอบรมปฐมนิเทศ และสิ่งอำนวยความสะดวก มีความเหมาะสมอยู่ในระดับมาก 3. ด้านกระบวนการ พบว่า ในด้านการบริหารและการบริการหลักสูตร จัดการเรียนการสอน สื่อการเรียนรู้ และวิธีการวัดและประเมินผล มีความเหมาะสมอยู่ในระดับมาก 4. การประเมินผลผลิต พบว่า ด้านผู้เข้ารับการอบรมปฐมนิเทศ มีทัศนคติที่ดีต่อองค์กรมากขึ้น และมีมนุษย์สัมพันธ์ที่ดีกับผู้อื่นมากขึ้น มีความเหมาะสมอยู่ในระดับมาก The purpose of this research was to evaluation an orientation program for new employees in Total Access Communication Public Company Limited by CIPP Model. The research instruments were an analysis form for data collection and three curriculum evaluation forms. The population was organizer, trainer, trainer assistant, new employees and persons of head section employees. Total population was 72 persons in number. The data were analyzed by percentage, arithmetic mean and standard deviation. Research findings were as follows: 1. Context evaluation showed that the curriculum objectives were related to external factors. The content of we provide digital communication, enabling everyone to improve their better lives. Objective and course outline and criteria of evaluation were rated at the high level of appropriated. 2. Input evaluation showed that the trainer new employee and facility were rated at the high level of appropriation. 3. Process evaluation showed that the administrative process, instructional activities instructional media and the measurement and evaluation were rated at the high level of appropriation. 4. Product evaluation showed that the new employees have better attitude for the firm and more friendliness to others were rated at the high level of appropriation.